2018
DOI: 10.1016/j.euromechsol.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

On the validity range of strain-gradient elasticity: A mixed static-dynamic identification procedure

Abstract: Wave propagation in architectured materials, or materials with microstructure, is known to be dependent on the ratio between the wavelength and a characteristic size of the microstructure. Indeed, when this ratio decreases (i.e. when the wavelength approaches this characteristic size) important quantities, such as phase and group velocity, deviate considerably from their low frequency/long wavelength values. This well-known phenomenon is called dispersion of waves. Objective of this work is to show that strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 35 publications
0
51
0
Order By: Relevance
“…A weak-scale separation ratio ( = m M = 1 8 ) is considered for producing both the numerical and the experimental sample. This ratio lies between the bounds identified in [33] and is chosen so as to magnify the higher-order kinematics. For both materials, numerical uniaxial tension tests are performed in order to design the real experiment.…”
Section: Organization Of the Papermentioning
confidence: 99%
See 1 more Smart Citation
“…A weak-scale separation ratio ( = m M = 1 8 ) is considered for producing both the numerical and the experimental sample. This ratio lies between the bounds identified in [33] and is chosen so as to magnify the higher-order kinematics. For both materials, numerical uniaxial tension tests are performed in order to design the real experiment.…”
Section: Organization Of the Papermentioning
confidence: 99%
“…In the same reference, it is shown that an extension of classical elasticity, called strain-gradient elasticity, is able to model the observed phenomenon. In [33], the validity range of this enrichment is studied. It results that the use of a strain-gradient continuum as an overall medium improves the continuous description for scale separation ratios ( = m M ) between 1/6 and 1/20.…”
Section: Introductionmentioning
confidence: 99%
“…For more details about the mechanics of generalized continua, see [5,75,180]. The study of structures made of architectured materials has been the object of intensive research in the last few years [168], and has resulted in promising results concerning the development of architectured metamaterials for acoustic [175,177] and elastodynamic applications [174,176].…”
Section: Discussionmentioning
confidence: 99%
“…and the projections on the tangent plane to the deformed surface as well as on the normal direction n. The identification of the introduced material parameters may be performed using the methods discussed in [56][57][58][59][60][61][62].…”
Section: Pantographic Sheets With Initially Cycloidal Fibersmentioning
confidence: 99%